BET ON GREEN: A COMMENT ON THE LEGISLATION-OF-ORIGIN OF AN INVESTMENT AND ITS EFFECTS ON INVESTMENTS IN THE CANNABIS INDUSTRY - Barba Radanovich, José Miguel (2024)
The present study aims to question the allocation of burdens and obligations within the realm of Investment Treaties (AIIs), starting from the analysis of an obvious and specific counterexample: the protection of the right to free transfer of assets and return on investments concerning cannabis investments. When investments are made in the cannabis industry, the protection offered by the host State of the investment is only half of the mandate, as it will be the duty of the home State of the investment to ensure that the investor can legitimately repatriate the legitimate returns of their investment to their home State. The essay establishes the framework from the perspective of investment protection law, explores possible justifications for States to restrict the right guaranteed by the BIT, and concludes with brief conclusions and recommendations.